Reaksi Pasar Terhadap Peraturan Kemenhub Nomor PM/13/Tahun/2021 Pada Perusahaan Transportasi dan Logistik - Ayu Indah Kartika Dewi, I Gusti; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
The research aims to find out whether there is a market reaction to the announcement of the Minister of Transportation Regulation Number 13 of 2021 concerning transportation control during the Eid al-Fitr period. The market reaction in this research is seen from the abnormal return obtained from the difference between the expected return and the realized return. Expected return in research is estimated using the mean-adjusted model. The research was conducted using the event window for 7 days, namely 3 days before the event date, on the event date, and 3 days after the event. Based on the test results, it was obtained that the results of the announcement of the Ministry of Transportation Regulation Number 13 of 2021 did not get a reaction from the market, which was indicated by the cumulative abnormal return which was not significant during the observation period. Keywords: Market Reaction; Event Studies; Abnormal Returns; Ministerial regulation; Prohibition on returning to one's home area.